Beclin 1 Gene Transfer Activates Autophagy and Ameliorates the Neurodegenerative Pathology in α-Synuclein Models of Parkinson's and Lewy Body Diseases - Spencer, Brian (Society for Neuroscience, 2009)
Accumulation of the synaptic protein α-synuclein (α-syn) is a hallmark of Parkinson's disease (PD) and Lewy body disease (LBD), a heterogeneous group of disorders with dementia and parkinsonism, where Alzheimer's disease and PD interact. Accumulation of α-syn in these patients might be associated with alterations in the autophagy pathway. Therefore, we postulate that delivery of beclin 1, a regulator of the autophagy pathway, might constitute a strategy toward developing a therapy for LBD/PD. Overexpression of α-syn from lentivirus transduction in a neuronal cell line resulted in lysosomal accumulation and alterations in autophagy. Coexpression of beclin 1 activated autophagy, reduced accumulation of α-syn, and ameliorated associated neuritic alterations. The effects of beclin 1 overexpression on LC3 and α-syn accumulation were partially blocked by 3-MA and completely blocked by bafilomycin A1. In contrast, rapamycin enhanced the effects of beclin 1. To evaluate the potential effects of activating autophagy in vivo, a lentivirus expressing beclin 1 was delivered to the brain of a α-syn transgenic mouse. Neuropathological analysis demonstrated that beclin 1 injections ameliorated the synaptic and dendritic pathology in the tg mice and reduced the accumulation of α-syn in the limbic system without any significant deleterious effects. This was accompanied by enhanced lysosomal activation and reduced alterations in the autophagy pathway. Thus, beclin 1 plays an important role in the intracellular degradation of α-syn either directly or indirectly through the autophagy pathway and may present a novel therapeutic target for LBD/PD.